2022
DOI: 10.3390/vetsci9120653
|View full text |Cite
|
Sign up to set email alerts
|

Rothia nasimurium as a Cause of Disease: First Isolation from Farmed Chickens

Abstract: Rothia nasimurium is a facultative anaerobic Gram-positive coccus belonging to the Rothia genus of the Micrococcaceae family. While Rothia nasimurium is considered an opportunistic pathogen, to date few studies have investigated its pathogenicity and drug resistance. In January 2022, chickens at a poultry farm in China’s Xinjiang Uygur Autonomous Region became ill and died. Treatment with commonly used Chinese medicines and antibiotics was ineffective, causing economic losses to the poultry farm. In order to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Notably, among the 24 genera of microbes presented in drake semen, 8 genera that mainly originated from the environment and cloaca were pathogenic microbes. Achromobacter is a key pathogen causing lung injury ( Veschetti et al, 2022 ; Zhou et al, 2023b ); Aerococcus not only associated with urinary tract and bloodstream infections in human ( Tai et al, 2021 ), but also has been reported to be associated with infectious diarrhea in poultry ( Khafagy et al, 2023 ); and Corynebacterium ( Enurah et al, 2016 ), Enterococcus ( Dolka et al, 2017 ), Kocuria ( Yang et al, 2021 ; Ziogou et al, 2023 ), Pseudomonas ( Pattison et al, 2008 ), Rothia ( Zhang et al, 2022 ), and Staphylococcus infections could affect lots of diseases such as haemorrhagic inflammation of the upper respiratory tract, vertebral abscess, necrotic enteritis, and hepatomegaly ( Szafraniec et al, 2022 ), etc. These results suggest that the negative effects of AI in the duck industry may be due to import the harmful microbes into the reproductive tract of female ducks.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, among the 24 genera of microbes presented in drake semen, 8 genera that mainly originated from the environment and cloaca were pathogenic microbes. Achromobacter is a key pathogen causing lung injury ( Veschetti et al, 2022 ; Zhou et al, 2023b ); Aerococcus not only associated with urinary tract and bloodstream infections in human ( Tai et al, 2021 ), but also has been reported to be associated with infectious diarrhea in poultry ( Khafagy et al, 2023 ); and Corynebacterium ( Enurah et al, 2016 ), Enterococcus ( Dolka et al, 2017 ), Kocuria ( Yang et al, 2021 ; Ziogou et al, 2023 ), Pseudomonas ( Pattison et al, 2008 ), Rothia ( Zhang et al, 2022 ), and Staphylococcus infections could affect lots of diseases such as haemorrhagic inflammation of the upper respiratory tract, vertebral abscess, necrotic enteritis, and hepatomegaly ( Szafraniec et al, 2022 ), etc. These results suggest that the negative effects of AI in the duck industry may be due to import the harmful microbes into the reproductive tract of female ducks.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the opportunistic pathogen Rothia nasimurium was first in the PM2.5 samples at 13.6%, and it can infect animals such as dogs, pigs, ducks, rabbits, and geese. The bacterium was isolated from captive chickens and geese for the first time and was found to be multidrug resistant by drug sensitivity test and animal regression test, resulting in severe hair loss in chickens and geese [68,69]. Staphylococcus aureus (0.46%) is a kind of pathogen that can cause primary infections in humans or animals, leading to severe clinical conditions such as bacteremia and sepsis [70].…”
Section: Discussionmentioning
confidence: 99%
“…Rothia nasimurium is a facultative anaerobic gram-positive coccus and part of the commensal flora of humans and other animals. Until recently, R. nasimurium was reported to be an opportunistic pathogen to ducks ( Wang et al, 2021 ) and chickens ( Zhang et al, 2022 ). Here, R. nasimurium strains were recovered from not only ducks and chickens but also geese.…”
Section: Discussionmentioning
confidence: 99%